Comments on "estimating income variance by probability sampling: A case study by Shah and Aleem" - Jamal Abdul Nasir; M. H. Tahir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
In this article, we wish to write comments on recently published article "Shah, A.A. and Aleem, M. (2010). Estimating income variances by probability sampling: a case study. Pakistan Journal of Commerce and Social Sciences, 4(2), 194-201", which suggest improvement as well as criticism on the paper and also contribute effectively towards journal repute and ranking.
Keywords: 330